THE POSTCOLONIAL OTHERNESS TRANSLATED INTO A „NON-COLONIAL” LANGUAGE - Czernik, Jakub (Porównania, 2018)
This paper aims to describe the mechanisms of translating postcolonial literature into a “non-colonial” language, transmitting a text from languages and cultures which take part in a (post)colonial clash. These issues are illustrated with the examples taken from Polish translations of Chinua Achebe’s Things Fall Apart and Salman Rushdie’s The Satanic Verses.